2006
DOI: 10.1007/bf03027711
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution behavior of zirconia-refractories during continuous casting of steel

Abstract: Dissolution behavior of ZrO2-graphite refractories used in a submerged entry nozzle (SEN) during continuous casting of steel was investigated using the rotating cylinder method. In the present work, the dissolution rate of the zirconia-graphite rod was determined by measuring the corrosion depth of the rod after a given immersion time. It was found that the dissolution rate was slow at the surface where molten flux alone is contacted, but much higher at the region that contacts the interface of the molten flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…For continuous casting of steel, the refractory used for the SEN plays a very important role as it is the last refractory in contact with the liquid steel. Therefore, the quality of the steel products will be deteriorated or the casting process may fail unless SEN can withstand thermal shock or corrosion attack from the liquid steel and molten flux 7–10 . Using the dipping bar rotation method, Bui et al 10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For continuous casting of steel, the refractory used for the SEN plays a very important role as it is the last refractory in contact with the liquid steel. Therefore, the quality of the steel products will be deteriorated or the casting process may fail unless SEN can withstand thermal shock or corrosion attack from the liquid steel and molten flux 7–10 . Using the dipping bar rotation method, Bui et al 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the quality of the steel products will be deteriorated or the casting process may fail unless SEN can withstand thermal shock or corrosion attack from the liquid steel and molten flux 7–10 . Using the dipping bar rotation method, Bui et al 10 . concluded that the dissolution rate of ZrO 2 –graphite refractory increased with the increase of rod rotating speed and the presence of fluoride (F −1 ) and Na 2 O in flux.…”
Section: Introductionmentioning
confidence: 99%
“…During the manufacture of the steel, an intense erosion of the outer wall of the SEN has been detected, mainly the one that comes in contact with the fluxes that form the slag of the mold [4]. The mechanisms of wear have already been described [5] and discussed in later studies [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 97%
“…[6][7][8] Although ZrO 2 -C materials with good corrosion resistance have been used on the outside of nozzle as slag-line materials, the corrosion problem still exists. [6,7,9,10] This phenomenon not only limits the production efficiency of continuous casting but also brings hidden dangers to production safety.…”
Section: Introductionmentioning
confidence: 99%